Przemiany wzorów osobowych żołnierzy w świetle procesu profesjonalizacji Wojska Polskiego - Miler-Slawiczek, Hanna (Studia Edukacyjne, 2015)
The article raises the question about the transformation of personal patterns of Polish soldiers in relation to the total organization of the armed forces at the turn of the 20th and 21st centuries. Presented is an analysis of the results of research on the personal characteristics of soldiers, in the light of empirical research undertaken by W. Horyn, W. Chojnacki, R. Kaluzny, W. Chudy, J. Maciejewski, I. Wolska-Zogata. Referring to the process of professionalization in military, special attention was paid in the article on the development of appropriate character traits for soldiers, required from the officers. The desirable characteristics of a modern soldier of the Polish Armed Forces In the light of normative documents, were highlighted and described. The postulates in the area of the professionalization of the military and reference to the soldier’s personal-professional profile were distinguished.